Teologia Pembebasan: Kajian Peranan Penting Gereja Dalam Memerdekakan Masyarakat Dari Kemiskinan - Martin Luther Manao; Abdon A. Amtiran (Melo: Jurnal Studi Agama-agama, 2021)
This research was conducted to find out how the role of the church in liberating society from poverty. The problem of poverty in the church base areas in Indonesia is a real problem and continues from year to year. Poverty is a human problem. The church as the salt and light of the world is here to make an impact and bring about change. The research uses a qualitative approach by searching literature and field facts to respond to the conditions of poverty and how the church plays a role in liberating people from poverty. The results of the study show the importance of the church's role in bringing change to people who experience poverty. The church can play a role in two things, namely: first, with a political approach, both in terms of realm power and in terms of the good common. Second, the educational approach is to become a facilitator for the community in conducting job skills trainings.